2008
DOI: 10.1002/chem.200701652
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Decarboxylation of β‐Keto Esters with Pd/Amino Alcohol Systems: Successive Metal Catalysis and Organocatalysis

Abstract: The kinetics and mechanisms of one-pot cascade reactions of racemic beta-keto esters to give chiral ketones in the presence of Pd/C-chiral amino alcohol catalyst systems were studied. Transformation of 2-methyl-1-tetralone-2-carboxylic acid benzyl ester (1) into 2-methyl-1-tetralone (4) in the presence of Pd/C and cinchona alkaloids or ephedrine was chosen as a model reaction. After the first reaction step, the Pd-catalysed debenzylation of 1 to afford the corresponding beta-keto acid (2), there are two possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…11,12 Interestingly, Baiker and co-workers showed that the reaction of such a β-ketoacid with AH* leads to the corresponding diastereomeric ammonium β-ketocarboxylates, and that their subsequent evolution towards the ketone proceeds at different rates. 13 According to these authors, this evolution would implicate the protonation of the ammonium salts by a second molecule of AH*, which would occur from the side opposed to their carboxylate unit and simultaneously with the breaking of the C-CO 2 bond. 13 They also assumed that the Pd/AH*-mediated domino reaction of a benzyl β-ketoester involves the corresponding β-ketoacid as the only intermediate responsible of the enantioselection, and its transformation via their concerted mechanism proposal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Interestingly, Baiker and co-workers showed that the reaction of such a β-ketoacid with AH* leads to the corresponding diastereomeric ammonium β-ketocarboxylates, and that their subsequent evolution towards the ketone proceeds at different rates. 13 According to these authors, this evolution would implicate the protonation of the ammonium salts by a second molecule of AH*, which would occur from the side opposed to their carboxylate unit and simultaneously with the breaking of the C-CO 2 bond. 13 They also assumed that the Pd/AH*-mediated domino reaction of a benzyl β-ketoester involves the corresponding β-ketoacid as the only intermediate responsible of the enantioselection, and its transformation via their concerted mechanism proposal.…”
Section: Methodsmentioning
confidence: 99%
“…13 According to these authors, this evolution would implicate the protonation of the ammonium salts by a second molecule of AH*, which would occur from the side opposed to their carboxylate unit and simultaneously with the breaking of the C-CO 2 bond. 13 They also assumed that the Pd/AH*-mediated domino reaction of a benzyl β-ketoester involves the corresponding β-ketoacid as the only intermediate responsible of the enantioselection, and its transformation via their concerted mechanism proposal. 13 We were not confident in this mechanism of the enantioselective reaction of benzyl β-ketoesters, which was based on computational studies from Strassner et al on the enantioselective decarboxylation of a Naproxen intermediate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the same level of selectivity was achieved compared to Muzart/H enins work. However, Baiker concluded from a thorough mechanistic study to an organocatalytic process by the cinchona alkaloid alone, the Pd being only necessary for the initial debenzylation of the ester [32].…”
Section: Palladium-catalyzed Edpmentioning
confidence: 99%
“…95 Kinetic studies of decarboxylation by NMR, IR and UV spectroscopy using cinchona alkaloids confirmed that following hydrogenolysis the dominant reaction route was catalysed by the chiral compound in the liquid phase as a homogeneous asymmetric organocatalytic reaction (Scheme 2). 96 Recently, asymmetric cascade reactions using combinations of a soluble chiral organocatalyst and supported Pd catalysts were developed for the preparation of chiral five membered unsaturated cyclic compounds. 97 Good yields and high stereoselectivities were obtained in reactions of cinnamaldehyde derivatives (6) with propargylic C-, O-or N-nucleophiles (7,9,11), leading to the formation of cyclopentene, dihydrofuran or pyrroline derivatives (Scheme 3).…”
mentioning
confidence: 99%